Gambaran sindrom metabolik pada pasien gangguan jiwa yang dirawat di rumah sakit jiwa provinsi Bali - I Putu Arya Giri Prabawa; Putu Kristalina Witari; I Wayan Yuna Ariawan (Intisari Sains Medis, 2019)
Introduction: Metabolic syndrome (MS) is a constellation of various disorders that can increase the risk of heart disease. MS is known to increase morbidity and mortality rates in psychiatric patients. However, MS in the population of mental disorders, especially in Bali, is still not well known.Methods: A cross-sectional analytic descriptive study was conducted in psychiatric patients treated at Bali Provincial Mental Hospital from January 2018 to February 2018. Inclusion criteria included inpatients who diagnosed with mental disorders based on DSM-IV criteria and those who had MS based on the National Cholesterol Education Program Adult Treatment Panel (NCE ATP III) criteria.Results: A total of 245 samples were included in this study with the prevalence of MS was 48.6%. According on sex, female had higher proportion among MS patients than male (42.8% vs 60.7%). In addition, the age group > 65 years had the highest frequency (75%) suffered from MS followed by age group of 45-65 years (54,9%). Based on the class of antipsychotic administered, MS patients with typical antipsychotic drug classes had the highest frequency, followed by the atypical group and combination of atypical and typical (49.4%, 49.3%, and 46.2%, respectively). Among MS patients, most of them had obesity (87.3%), followed by dyslipidemia, hypertension and impaired fasting glucose (76.4%, 65.5%, and 60.4%, respectively).Conclusion: There is a high prevalence of metabolic syndrome among patients with mental disorder admitted to the Mental Hospital of Bali Province. Comprehensive multidisciplinary co-operation is required in the treating those with metabolic syndrome as comorbid.